The Attitude and Readiness Towards Interprofessional Education (IPE) Among Medical Teachers of Universitas Muhammadiyah Jakarta - Ramadini, Savira Dwi; Oktarina, Oktarina (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2021)
Background: Geriatric has multi-problems which need inter-disciplinary supports including collaboration among health professionals. To realize the importance of collaboration among health workers is to encourage collaboration since educational process. Teachers play an important role in conducting an Interprofessional Education (IPE). Purposes: To describe the attitudes and readiness of medical teachers of Universitas Muhammadiyah Jakarta (UMJ) towards IPE in 2019. Methods: The subjects of the study were medical teachers of UMJ with a sample size of 34 respondents. It was conducted at UMJ on November-December 2019. The instrument used for measuring the variable of attitude is the Attitudes toward Health Care Teams Scale (ATHCTS), whilst Readiness for Interprofessional Learning Scale (RIPLS) questionnaire was for the readiness. Results: It was found respondents who had attitudes in the good and fairly good categories were 62% and 38% respectively. Based on their state of readiness, 85% of the respondents were adequate, 15% moderate, and none not ready. Conclusion: Most of the respondents had a good attitude and ready for IPE. It was found that the aspects of the role in the team are mostly fairly good compared to aspects of values in the team and efficiency in the team which are mostly in the good category. The readiness showed adequate state in 2 aspects which are teamwork and collaboration and professional identity, whilst the aspect of role and responsibility was moderate. Consequently, improvement should be directed for the attitude to play a role in the team and the readiness in role and responsibility aspects.